BURGOS EN EL NO-DO: DE CAPITAL DE LA CRUZADA A CIUDAD INDUSTRIAL - Dra. Clara SANZ-HERNANDO (Fonseca, Journal of Communication, 2023)
The representation of Burgos in the official news reels of the state-controlled agency, Noticiarios y Documentales (NO-DO) [News and Documentaries], is studied through the political news reels released during the years of Francoism (1939-1975). The topics covered, their treatment, and their changes are determined through a qualitative methodology.